Civic Education Pesantren Salaf di Madura : Sinergi Pendidikan Karakter dan Upaya Deradikalisasi - Maimun, Maimun; Haris, Abdul (TADRIS: Jurnal Pendidikan Islam, 2021)
This study aims to describe the internalization of civic education, especially in the effort to foster the spirit of nationalism and love the country from two salaf Islamic boarding schools in Madura between the al-Mubarok Lanbulan Tambelangan Islamic Boarding School in Sampang and the Islamic Boarding School of Al-Is'af Kalabaan Guluk-Guluk Sumenep. The research subjects who became the information center consisted of caregivers, asatidz and administrators with data collection techniques including interviews, observation and documentation. For data analysis, the researcher used Miles and Huberman's interactive analysis technique. To test the validity of the data, it is used triangulation technique. The results showed that the internalization of civic education in these pesantrens was conveyed in three ways; First, through learning. The students are taught the morals of the state and love the country through the clasical book of 'Idhatun Nasyi'in and through civics education learning in the equality education system applied at the al-Mubarok Islamic boarding school. Meanwhile, for pesantren al-Is'af, it is applied through additional explanations in book recitation conditionally. Second, through the extra activities, including; organizing, bahsul masail, flag ceremony on 17 of August and the commemoration of the national santri day at al-Mubarok, as well as through bahsul masail and muhadara activities at the al-Is'af boarding school. Third, through social activities of students in the internal boarding school.